KOMPARASI PEMBELAJARAN BERBASIS EKSPERIMEN DAN PEMODELAN FISIKA DALAM SETTING PENDEKATAN SAINTIFIK PADA KELAS X SMAN 13 PADANG - Putri Heryeni; Syakbaniah Syakbaniah; Nurhayati Nurhayati (PILLAR OF PHYSICS EDUCATION, 2015)
This research is motivated not optimal learning activities of students. Learning activities have not been able to improve the ability of learners to be able to think independently, so that learning becomes meaningful. This research aimed to investigate the differences of learners using experiments based learning and physics modeling based learning in setting the scientific approach. This research is a quasi-experimental research with the design of randomized control group design only.Sampling used purposive sampling technique. Results of research on the experimental class 1 gained an average of competence knowledge = 75.75 and the experimental class 2 = 70.84, competence experimental attitude in class 1 = 84.94 and the experimental class 2 = 81.69, competency skills in experimental class 1 = 84.25 and the experimental class 2 = 81.50. After t test for second grade sample on the competence of knowledge, attitudes, and skills respectively 10.97, 7.39, 4.23 greater than the table = 1.66. It can be concluded that the working hypothesis which says "There is a significant difference between the use of learner competence-based learning and learning experimental physics-based modeling in setting the scientific approach in Senior High School grade X” the real level 0,05